2010
DOI: 10.1159/000313440
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk and Neuroradiological Profiles in Asymptomatic Vertebrobasilar Dolichoectasia

Abstract: Background: Clinicoradiological variability of vertebrobasilar dolichoectasia (VBD) is known. Little is known about cardiovascular disease (CVD) risk and neuroradiological profiles of asymptomatic VBD. Methods: A total of 7,345 adults (5,534 men and 1,811 women) underwent physical checkup (PC) and brain magnetic resonance (MR) studies between 2004 and 2007. Asymptomatic VBD was diagnosed by neurological examination and MR angiography. Neuroradiological features were analyzed in VBD subjects. CVD risk factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 32 publications
(96 reference statements)
2
58
1
3
Order By: Relevance
“…17,18 The prevalence of BA or intracranial dolichoectasia is 3.1% to 13.9% in patients with ischemic stroke 5,11 and 1.3% in healthy people. 7 In the present study, patients with a BA diameter >4.5 mm made up only 0.8% of the 493 total patients, of whom 24.7% had a history of ischemic stroke. We defined BA diameter as the minor axis of the BA diameter on the axial MRI images because the BA sometimes extends obliquely and is shaped like an ellipse in cross section, which may be a reason for the smaller size of the BA in this study.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…17,18 The prevalence of BA or intracranial dolichoectasia is 3.1% to 13.9% in patients with ischemic stroke 5,11 and 1.3% in healthy people. 7 In the present study, patients with a BA diameter >4.5 mm made up only 0.8% of the 493 total patients, of whom 24.7% had a history of ischemic stroke. We defined BA diameter as the minor axis of the BA diameter on the axial MRI images because the BA sometimes extends obliquely and is shaped like an ellipse in cross section, which may be a reason for the smaller size of the BA in this study.…”
Section: Discussionmentioning
confidence: 48%
“…Several studies have shown that dolichoectasia is associated with cerebral small-vessel diseases (CSVDs), such as lacunar infarct, état criblé, and white matter lesions. 5,6 In addition, aging, 5 atherosclerotic risk factors, 5,7 and some genetic factors that affect connective tissues [8][9][10] have been shown to be related to dolichoectasia. Dolichoectasia is most often observed in the basilar artery (BA) 5,11,12 and is associated with intracranial bleeding, stroke mortality, and cardiovascular death.…”
mentioning
confidence: 99%
“…9 Dolichoectasia is strongly associated with aging and vascular risk factors. 10 Rare case reports describe diffuse involvement of all intracranial vessels, 11 and onset in childhood and infancy has been reported, 12 suggesting underlying genetic or congenital causes. This relatively rare vessel anomaly (affecting 1% to 6% of asymptomatic people in scan and autopsy series 10,13,14 ) is linked to vascular risk factors and thus is likely preceded by a more common forme fruste stage of vessel enlargement.…”
Section: See Accompanying Article On Page 2240mentioning
confidence: 99%
“…[4] Vertebrobaziler arter dolikoektazilerinin (VBD) toplumdaki insidansı %0.06-%5.8 arasında rapor edilmektedir. [5][6][7] Olguların büyük çoğunluğu asemptomatiktir ve sıklıkla başka nedenlerle yapılan kraniyel görüntülemelerde, özellikle 40 yaş üzerindeki hipertansif hastalarda, tesadüfen gözlenir. [7] Semptomatik olgulardaki bulgular serebral iskemiye, kanamaya ya da bası etkisine (beyin sapı, üçüncü ventrikül veya kraniyel sinir kökleri) bağlı olarak gelişir.…”
Section: Introductionunclassified
“…[5][6][7] Olguların büyük çoğunluğu asemptomatiktir ve sıklıkla başka nedenlerle yapılan kraniyel görüntülemelerde, özellikle 40 yaş üzerindeki hipertansif hastalarda, tesadüfen gözlenir. [7] Semptomatik olgulardaki bulgular serebral iskemiye, kanamaya ya da bası etkisine (beyin sapı, üçüncü ventrikül veya kraniyel sinir kökleri) bağlı olarak gelişir. VBD'ye bağlı başağrısı olguları oldukça nadirdir ve genellikle tri-PAIN A RI geminal nevralji kliniği ile prezente olurlar.…”
Section: Introductionunclassified